Darowizny na rzecz małżonków w świetle regulacji prawnej obowiązującej w Królestwie Polskim - Wiśniewska-Jóźwiak, Dorota (Czasopismo Prawno-Historyczne, 2011)
Donations in the Kingdom of Poland were regulated by the Napoleonic Code. However, apart from a couple of general rules, the Napoleonic Code did not provide for any special regulation that would be exclusively applicable to the specific kind of donations such as donations made by one spouse to the other. Acts-in-law pertaining to donations could be executed either in the same deed (notarial act) together with the pre-nuptial agreement, or as a separate deed. What was particularly interesting as well as extremely complicated were marriage contracts which required a distinction to be drawn among three types of acts-in-law, namely: donations of current property, donations of future property, and donations of current and future property combined, where the future property was understood as inheritance arising at the death of the testator. Performing of this unique act-in-law was still less complicated than making a contract to donate property, while the testators could be not only the spouses themselves but third parties as well.